ALLOMETRIC RELATIONSHIPS IN OLIVA OLIVA (LINNE) - kasinathan, K; Maruthamuthu, S; Tagore, J (Indian Journal of Fisheries, 2011)
AUometric relationships between shell height, shell width, aperture height,aperture width, total animal weight, wet flesh weight, dry flesh weight and shellweight in Oliva oliva were subjected to correlation coefficient analysis and resultshave been discussed. Analysis of covariance revealed significant difference betweenregression equations of males and females. There is significant difference in growthbetween the male and female of this species which was observed thrcSugh Mahalanobis'D.2 test. When considered size-groupwise, the shell dimensions (shellheight and width) of males and females grow isometrically up to 35.9 mm in size